Setting the development agenda US foundations and the NPO sector in South Africa - Moyo, Bhenkinkosi (My University, 2006)
This thesis discusses the impact that the Ford, Mott, Kellogg and Open Society Foundations had on civil society organisations in South Africa in setting development priorities. The thesis tested first, the hypothesis that donors set the agenda for their grantees. Secondly, the thesis tested the assumption that aid facilitates grantees’ submission to donor interests. And in the process grantees lose their identity and focus. The research found that most of civil society organisations (CSOs) depended on international donors, in particular, foundations,for their operations. There was little mobilisation of resources from local citizens. As a result, CSOs were vulnerable to donor conditionalities and agendas. The four case studies and their selected beneficiaries show that most CSOs were not sustainable. If donors withdrew their support, a number of their grantees would curtail their work, close down or lose their vision and mission. In some cases CSOs changed their missions to follow the money, nevertheless, changing contexts and demands were also relevant factors. Although lack of sustainability for CSOs and their greater dependency on international donors made their agendas questionable, it also provided independence from internal political interference. CSOs also appeared more accountable to donors than to the constituencies they served. The Kellogg Foundation insisted that organisations had to toe the line to implement the Foundation’s agenda or risk losing funding. George Soros of the Open Society Foundation also called the shots. He set the agenda and his Foundations implemented it. This showed the power of direct intervention by a living donor who operated as a Programme Officer for all his foundations. The question of donor-dependency is closely linked to that of leadership. A number of organisations with good leaders attracted many donors. However the increase in donors, did not sustain these organisations, instead it made them vulnerable to many different donor demands. Thus, donor diversification was both an asset and a threat. However, good leadership prevented CSOs from collapse from lack of transparency, accountability and effectiveness. A temptation to ‘want to look like donors’, a process that is called ‘isomorphism’ by DiMaggio and Powell (1991) characterised many CSOs resulting in them losing their identity, mission and vision. There were positive aspects that international Foundations achieved in supporting civil society foundations. The Open Society Foundation worked to open up closed societies. It supported efforts that aimed at fostering democratic ideals, rule of law, social justice and open societies. The Ford Foundation supported efforts that strengthened civil society, promoted social justice and democracy. The Mott Foundation strengthened the capacity of the non-profit sector by developing in-country philanthropy. And the Kellogg Foundation supported community initiatives that aimed to tackle the causes of poverty. A negative development; however was that Foundations cultivated the culture of receiving rather than giving among their grantees. For this reason, the thesis suggested the development of ‘community philanthropy’ to sustain the non-profit (NPO) sector. Community philanthropy has the advantage of mobilising resources from domestic sources and taping into levels of social capital. Building on domestic sources would encourage a bottom up approach to development. I argue that local self-help initiatives such as stokvels, burial societies and saving clubs could serve as bases for the sustainability of the non-profit sector which suffered from donor dependency, unsustainability and poor leadership. Such an approach would make development ‘people-centered’ and encourage social responsibility among citizens to support their NPOs and its development initiatives.
Student Number: 0004062T Doctor of Philosophy Faculty of Humanities and Social Sciences
Keywords: Civil Society; Ford, Mott, Kellogg and Open Society Foundations; Development priorities; South Africa; Foreign policy; Donor funding; CSO; Donor dependency; Beneficiaries; Grantees; Isomorphism; Community philanthropy